Forecasting of structural transformations in heat affected zone steel of 15Kh2NMFA at anti-corrosion cladding - Lobanov, L.M.; Kostin, V.А.; Makhnenko, O.V.; Zukov, V.V.; Kostenevich, E.S. (Вопросы атомной науки и техники, 2020)
Using mathematical modeling based on existing parametric regression equations the prediction of microstructure-phase transformations in heat affected zone( HAZ) metal of base material (steel 15Kh2NMFA) of WWER-1000 reactor vessel in arc cladding of protective anti-corrosion layer was carried out as well as performed comparative analysis of modeling results with obtained experimental data of dilatometric and metallographic analysis. The comparison of results ensures formation of bainite-martensite structure in HAZ metal of WWER-1000 reactor vessel, however a value of content of martensite in calculation and experimental determination is different on ⁓ 40…50%. To clarify the calculated results, a thermokinetic diagram of the decomposition of supercooled austenite was constructed for characteristic cooling rates (3; 4, and 5 °C/s) during the welding/surfacing thermal cycle. As a result, adequate parameters of the microstructure-phase composition in the HAZ of steel 15Kh2NMFA at corrosion-resistant cladding were obtained.